(untitled) (Fiep Bulletin - online, 2014)
The changes the world has been going through in the last few years are very visible, especially in terms of bodyrelated issues. Today, obesity has achieved epidemic proportions, and a large part of society is at risk. This paper aims to study the representations of body image of people with morbid obesity who were submitted to bariatric (gastric bypass) surgery. A qualitative investigation was carried out by means of a case study. Bariatric surgery provides the obese with improvements in terms of not only their general health but also their self-esteem. However, those people usually see the surgery as a solution to all their problems, which is certainly not true. A search for a dream or ideal body takes place then, but rarely does it comes true. It is when that ideal is not attained that self-image deviations, frustration and depression may arise.